Workplace Violence Against Doctors in Bangladesh: A Content Analysis - Kader, Shirmin Bintay; Rahman, Md. Marufur; Hasan, Md. Khaledul; Hossain, Md. Mohibur; Saba, Jobaida; Kaufman, Sophia; Christopher, Enryka; Koly, Kamrun Nahar (Frontiers in Psychology, 2021)
Workplace violence in healthcare settings is a common global problem, including in Bangladesh. Despite the known presence of workplace violence in healthcare environments of developing countries, there is limited understanding of factors that lead to hospital violence in Bangladesh. This study aims to explore factors that influence incidents of violence against healthcare professionals in Bangladesh, as reported by doctors via social media forum. Content analysis was conducted on 157 reported incidents documented on “Platform,” the online social media most used by medical students and doctors in Bangladesh. Posts by doctors detailing experiences of physical or verbal violence at their workplace between July 2012 and December 2017 were included in this study. The majority of reported incidents were reported by male doctors (86%) and from government hospitals (63.7%). Findings show that primary health care centers experienced more violence than secondary and tertiary facilities. This may largely be due to insufficient human and other resources in primary care settings to meet patient demand and expectations. Most of the events happened at night (61%), and as a result, entry-level doctors like emergency duty doctors and intern doctors were commonly affected. Six themes were identified as vital factors in workplace violence against doctors: patients’ perspectives, delayed treatment, power practice, death declarations, extreme violence, and care-seeking behaviors. Most incidents fell under the categories of delayed treatment and power practice at 26.8% and 26.1% respectively. This study identified possible factors for reported violence in hospital settings. To address and reduce these incidents, hospital administrators should be aware of risk factors for violent behavior and design appropriate measures to prevent workplace violence. Further qualitative and quantitative research is needed to appropriately address the consequences of violence on healthcare workers and implement measures to mitigate these events.